Determination of the number of light neutrino species from single photon production at LEP - Dova, María Teresa (1998)
A determination of the number of light neutrino families performed by measuring the cross section of single photon production in eqey collision near the Z resonance is reported. From an integrated luminosity of 100 pby1 , collected during the years 1991–94, we have observed 2091 single photon candidates with an energy above 1 GeV in the polar angular region 458-u -1358. From a maximum likelihood fit to the single photon cross section, the Z decay width into invisible particles g is measured to be G s498"12 stat Ž . Ž. "12 sys MeV. Using the Standard Model couplings of neutrinos to the Z, the inv number of light neutrino species is determined to be N s2.98"0.07 stat Ž . Ž. "0.07 sys.